A preoperative serum signature of CEA+/CA125+/CA19‐9 ≥ 1000 U/mL indicates poor outcome to pancreatectomy for pancreatic cancer. Issue 9 (18th October 2014) - Liu, Liang; Xu, Huaxiang; Wang, Wenquan; Wu, Chuntao; Chen, Yong; Yang, Jingxuan; Cen, Putao; Xu, Jin; Liu, Chen; Long, Jiang; Guha, Sushovan; Fu, Deliang; et al.
<x xml:space="preserve">Abstract</x> Pancreatectomy is associated with significant morbidity and unpredictable outcome, with few diagnostic tools to determine, which patients gain the most benefit from this treatment, especially before the operation. This study aimed to define a preoperative signature panel of serum markers to indicate response to pancreatectomy for pancreatic cancer. Over 1000 patients with pancreatic cancer treated at two independent high‐volume institutions were included in this study and were divided into three groups, including resected, locally advanced and metastatic. Eight serum tumor markers most commonly used in gastrointestinal cancers were analyzed for patient outcome. Preoperative CA19‐9 independently indicated surgical response in pancreatic cancer. Patients with CA19‐9 ≥1000 U/mL generally had a poor surgical benefit. However, a subset of these patients still achieved a survival advantage when CA19‐9 levels decreased postoperatively. CEA and CA125 in the presence of CA19‐9 ≥1000 U/mL could independently predict the non‐decrease of CA19‐9 postoperatively. The combination of the three markers was useful for predicting a worse surgical outcome with a median survival of 5.1 months vs. 23.0 months (p < 0.001) for the training cohort and 7.0 months vs. 18.2 months (p < 0.001) for the validation cohort and also suggested a higher prevalence of early distant metastasis after surgery. Resected patients with this proposed signature showed no survival advantage over patients in the locally advanced group who did not receive pancreatectomy. Therefore, a preoperative serum signature of CEA+/CA125+/CA19‐9 ≥1000 U/mL is associated with poor surgical outcome and can be used to select appropriate patients with pancreatic cancer for pancreatectomy.